Who is the Real Addressee of Seneca’s Moral Letters to Lucilius? - Dikmonienė, Jovita (Literatūra, 2016)
Senecaʼs Moral Letters to Lucilius and Dialogues are the earliest surviving works of the ancient Stoics. Even though Seneca’s Moral Letters to Lucilius has attracted a great deal of scholarly attention, there is however disagreement in academia about to whom Seneca’s Moral Letters to Lucilius was actually addressed. For instance, some scholars (e. g., D. Dilytė, P. Grimal, etc.) argue that Lucilius was a real person and that the letters are real, whereas others (e. g., B. Inwood, M. T. Griffin etc.) claim that Lucilius is a literary character and consequently Senecaʼs Letters is literary fiction.Exploring various primary and secondary sources, this paper investigates the disagreement concerning the addressee in Seneca’s Moral Letters to Lucilius. The paper discusses both theories and analyses the influence of the ancient epistolary genre on Seneca’s writings. Moreover, in order to validate one of the theories, the author explores the Roman philosopher’s background, ideas of Stoicism, and the context and period during which the work was written.The article concludes that Seneca’s Moral Letters to Lucilius is a work addressed to the public. Letters is not merely a collection of personal correspondence between the two philosophers about the soul, virtue, and justice, but rather, as Miriam T. Griffin asserts, literary fiction. That Seneca always starts and ends his letters in the epistolary form of communication and always mentions that he has received a letter from Lucilius is not a valid argument to prove that Seneca actually corresponded with Lucilius. Such form conforms to the standards and requirements of the Classical epistolary genre. In fact, due to the lack of historical records in the text, it is likely that in his Letters, Seneca creates Seneca persona. As a result, we cannot be sure whether the author reveals his true feelings in the text or not.In various works of Seneca, Lucilius is characterised differently. In Naturales Quaestiones ambition is a feeling alien to Lucilius. In Letters however, Lucilius pursues a political career. The paper asserts that if Lucilius was indeed a former procurator of Sicily, in his fictional piece Seneca would not urge Lucilius to abandon his career. The paper proposes that the passage about resignation was added to the Letters to justify Seneca’s withdrawal and to prove that a true Stoic can remain useful to society even while living a private life. All things considered, Seneca’s Moral Letters to Lucilius is not the result of actual correspondence between the two philosophers, but is rather a work inspired by the letters of Epicurus and Cicero, as well as Stoic ideas. It is a carefully contrived Stoic text, written in epistolary form. It is also a perfect literary work designed for future generations.
Keywords: Seneca; letters; addressee; Stoicism; Epicurism